Peningkatan Persepsi Status Kesehatan Ibu Hamil melalui Konseling Pentingnya Pemanfaatan Layanan PPIA-HIV - Susi Sulastri; Endah Purwanti Handayani; Mona Safitri Fatiah (Jurnal Ners, 2025)
The spread of Human Immunodeficiency Virus (HIV) among pregnant women in Papua is quite high, around 2.3% compared to other provinces in Indonesia, which is due to the lack of interest of pregnant women to utilize servicesPPIA . This aims to analyze the effect of study counseling on improving the perception of the status of healthpregnant women on the importance of utilizing PPIA-HIV. This study used primary data taken directly from pregnant women who performed pregnancy checks at Independent Practitioner Midwife (BPMRodinda ) during the period July-December 2024, totaling 172 people with a research design in the form of Pre-experiment. Sampling of pregnant women using technique purposive sampling with a research questionnaire. This was study analyzed up to bivariate with Wilcoxon test. analysis the The results of the study found that around 76.8% of mothers who utilized the PPIA service not only that it turned out that the counseling method was able to improve the health perceptions of pregnant women before and after being given counselingbefore and after being given counseling which was marked by a p-value of 0.001, , where there was a difference in the average value of perceived susceptibilityperceived perceived benefit severity, and perceived barrier . Conclusion: providing counseling incentive to pregnant women can change the perceptions of pregnant women regarding the utilization of PPIA-HIV services.